Feasibility of modified double-layered suturing for a large mucosal defect after duodenal endoscopic submucosal dissection (origami method) - Masunaga, Teppei; Sasaki, Motoki; Murata, Shoma; Imura, Yuri; Minezaki, Daisuke; Tojo, Anna; Sakurai, Hinako; Iwata, Kentaro; Miyazaki, Kurato; Mizutani, Mari; Nishikawa, Michiko; Akimoto, Teppei; Takatori, Yusaku; Kawasaki, Shintaro; Matsuura, Noriko; Tomida, Hideomi; Nakayama, Atsushi; Sujino, Tomohisa; Takabayashi, Kaoru; Yahagi, Naohisa; Kato, Motohiko (Endoscopy, 2025)
A modified double-layered suturing procedure (origami method; OGM) can achieve robust closure, even for large mucosal defects, by folding the muscle layer using through-the-scope clips. This study aimed to evaluate the feasibility of OGM in duodenal endoscopic submucosal dissection (ESD).This retrospective, observational study was conducted at a tertiary care hospital. We reviewed cases of OGM attempted after duodenal ESD between June 2022 and April 2023. We excluded lesions located in the duodenal bulb or involving the major papilla. We measured the clinical characteristics and outcomes.OGM was attempted in 28 cases after duodenal ESD. The median mucosal defect size was 38 mm (range 26−110). Complete closure was achieved in 27 cases (96%), including the largest lesion. The median closure time was 16 minutes. There were no perforations caused by clips. Delayed perforation and bleeding were not observed. Among 28 cases, 21 underwent follow-up endoscopy 3–5 days after ESD, and the muscle layer remained folded in all cases.OGM achieved a high rate of complete closure even after duodenal ESD. Closure with OGM was robust enough to maintain the folded muscle layer for at least 3 days postoperatively.